GlobeSen:an interconnection framework of information-centric IoT - Bo CHEN; Liang LIU; Hua-dong MA (物联网学报)
Interconnection framework of information-centric IoT:GlobeSen was proposed,which implemented the efficient interconnection of sensor networks and Internet.According to the characteristic of weak network elements,such as wireless sensor nodes,and the spatio-temporal relationship of sensory data,an information-centric network protocol for sensor networks NDNs was designed.Then,a protocol translation mechanism in the gateway was designed to interconnect NDNs and NDNx that running in Internet.A prototype by using the TelosB wireless sensor node and ARM board was implemented,and the proposed design by deploying the prototype in the environment was evaluated.